Analysis of schematic structure of job application letters of a Malaysian company / Muhamad Izzat Rahim and Mazliyana Zainal Arifin - Rahim, Muhamad Izzat; Zainal Arifin, Mazliyana (Universiti Teknologi MARA, Pulau Pinang, 2014)
The study aims to investigate the schematic structure used by Malaysian job applicants in writing job application letters. Fifteen job application letters from a Malaysian company were analysed. The study adopted genre analysis method to analyse the letters. Bhatia (1993)’s move structure framework was used as the base to analyse the samples. It was found that Malaysians tend to use a six-move- structure in writing job application letters. In doing so, these writers left one move namely Move 5 which is using pressure tactics. This is different from Bhatia’s move structure which consists of seven moves. Conclusively there is variation in schematic structure of the analysed letters as compared to Bhatia’s. This variation is the result of the different in sociocultural norm of the community. However, the variation does not hamper the communicative purpose of the letters.